Sistem Informasi Rawat Jalan Klinik Cahaya Putera Siti - Abdillah, Muhamamd Abu (Politeknik Sawunggalih Aji, 2025)
A clinic is a health service facility that organizes and provides basic or specialist medical services needed to support health improvement. The purpose of making this system is to provide health facility services to the community that are more optimal, especially the outpatient information system process and data processing to make it faster and easier. This study uses data collection methods and direct observation (observation) at Cahaya Putera Siti Clinic to obtain data that will be used as an information system. The design used for making information systems uses PHP programming language, visual studio code and databases used in making this information system using MySQL. The conclusion of the results of the research in this Final Project is in the form of an outpatient information system that can be used to facilitate easier, faster and more accurate data processing. Cahaya Putera Siti Clinic faces challenges in providing efficient outpatient services due to manual administrative processes that often result in delays, duplication, and data inaccuracy. This study aims to develop a web-based outpatient information system to streamline patient registration, medical records, and clinic administration. The system was designed using the Waterfall Model, which consists of requirement analysis, system design, implementation, testing, and maintenance. PHP was employed as the programming language with MySQL as the database, while black box testing was conducted to validate the functionality of the system. The findings show that the developed system successfully improves data accuracy, reduces processing time, and generates more structured reports. By automating administrative workflows and integrating patient information, the system enhances service quality and reduces the workload of clinic staff. Overall, the outpatient information system provides a practical solution to optimize operational efficiency and is expected to support better healthcare delivery at Cahaya Putera Siti Clinic.